Primary Repair of Internal Carotid Artery Aneurysm Secondary to Kinking and Cystic Medial Degeneration. (May 2013) - Nenezic, Dragoslav; Tanaskovic, Slobodan; Radak, Djordje; Babic, Srdjan; Gajin, Predrag
Introduction: In this report, we aim to present a very rare case of internal carotid artery (ICA) aneurysm secondary to kinking and cystic medial degeneration. Case report: A 66-year-old female patient was admitted to our institution for multidetector computed tomography (MDCT) angiography of supra-aortic trunks. On admission, she complained of occasional dizziness; 2 months earlier ascending aorta reconstruction was done for aneurysmal disease. Color Doppler ultrasonography and MDCT arteriography revealed significant right ICA kinking associated with large aneurysm, 24.6 × 24.5 mm 2 in diameter. Aneurysm resection was done followed by ICA reconstruction by end-to-end anastomosis. Pathohistological findings of aneurysmal sac revealed cystical medial degeneration with inflammatory infiltrate mostly consisting of lymphocytes and fibrovascular proliferation. Conclusion: This is the first case that describes mutual contribution of cystic medial degeneration and ICA kinking in carotid aneurysm disease etiology successfully treated by aneurysm resection.